(untitled) (Research, Society and Development, 2021)
Objective: To identify the requirements for training the nursing team to act in urgent and emergency situations in Primary Health Care. Methodology: This is an integrative review, structured according to the PRISMA methodology. The research had as scenario a Family Health Unit, located in a neighborhood of the Railway Suburb of Salvador/Ba, participated in the research three Nurses and five Nursing Technicians, data were obtained through a questionnaire, through an instant messaging application for smartphone. Results: The sample was composed of nursing professionals, all participants stated that they have worked in emergency, of these only 75% were trained and only 37.5% qualified by the Municipal Health Secretariat and 50% feel able to act in emergency care, no participant uses the Manchester Scale during urgent and emergency care. With this analysis we can see the lack of security of professionals and the lack of practice and experience involving emergency situations. Final considerations: Training courses for all PHC nursing professionals are essential, since the lack of information on the subject can affect the assistance recommended by primary care.